Roundworms A Survey From Past to Present - Dogan, Nihal (IntechOpen, 2023)
The first roundworm identified in humans was Ascaris, described by Linnaeus in 1758. Rudolphi's 1808 classification was the first to describe the Nematoidea. With the development of new molecular techniques, classification and phylogenetic research have also frequently changed; in 2019 a new classification, the phylum Nematoda, was created based on evolutionary relationships, developmental and morphological features and recent molecular evidence. Nematodes, which include hookworms, whipworms, threadworms, and soil-borne worms, are one of the oldest disease-causing creatures, dating back to Ancient Greek, Roman and Mesopotamian civilizations. Most commonly affecting children and women, the disease causes developmental disorders, cognitive impairment and death, with symptoms primarily affecting the organs they inhabit. In this book, the historical background, biology, transmission routes and geographical distribution of some roundworms affecting human health are discussed.